Decarboxylative Fluorination of Arylcarboxylic Acids Promoted by ortho‐Hydroxy and Amino Groups2. Issue 6 (17th April 2018) - Wang, Dinghai; Yuan, Zheliang; Liu, Qilun; Chen, Pinhong; Liu, Guosheng
Abstract: A novel decarboxylative fluorination process has been developed for the synthesis of ortho ‐hydroxy/amino arylfluorides from salicylic acid analogs, in which the ortho ‐hydroxy/amino group plays an important role in the transformation. In addition, various arylfluorides are obtained in good to excellent yields under mild conditions. Abstract : A novel decarboxylative fluorination process has been developed for the synthesis of ortho ‐ hydroxy/amino arylfluorides from salicylic acid analogs, in which the ortho ‐hydroxy/amino groups play an important role in the transformation. In addition, various arylfluorides are obtained in good to excellent yields under mild conditions.